2023
DOI: 10.1007/s12020-023-03517-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein in early pregnancy and gestational diabetes mellitus: a prospective cohort study

Tingyu Luo,
Hongyan Chen,
Huixin Wei
et al.

Abstract: The relationship between dietary protein intake and the risk of gestational diabetes mellitus (GDM) remains inconsistent and unclear. Here, we examined the correlation between the various sources of protein intake among Chinese pregnant women and GDM. MethodsThis prospective cohort study included 1060 pregnant women at 6-13 + 6 weeks of gestation from Guangdong Provincial Hospital for Women and Children, South China. The participants' intake of dietary protein was assessed using a validated quantitative food f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Of late a whole host of dietary strategies have been or are being studied to investigate potential links with alterations in GDM risk, including variations of the Mediterraneanstyle diet [14,15], high-fiber diets [16], diets with high complex carbohydrate contents [17], plant-based dietary patterns [18], diets high in probiotic yogurt contents [19], and diets with high colorful fruit and vegetable contents [20]. Further, observational dietary studies have reported associations between GDM risk and protein intake in early pregnancy (higher risk with increased early animal protein intakes and lower risk with increased early plant protein intakes [21]). Other dietary approaches currently being tested include a pre-pregnancy lifestyle intervention involving an aerobic exercise regime combined with time-restricted eating of less than ten hours a day, in women who are contemplating pregnancy and have risk factors for GDM [22].…”
mentioning
confidence: 99%
“…Of late a whole host of dietary strategies have been or are being studied to investigate potential links with alterations in GDM risk, including variations of the Mediterraneanstyle diet [14,15], high-fiber diets [16], diets with high complex carbohydrate contents [17], plant-based dietary patterns [18], diets high in probiotic yogurt contents [19], and diets with high colorful fruit and vegetable contents [20]. Further, observational dietary studies have reported associations between GDM risk and protein intake in early pregnancy (higher risk with increased early animal protein intakes and lower risk with increased early plant protein intakes [21]). Other dietary approaches currently being tested include a pre-pregnancy lifestyle intervention involving an aerobic exercise regime combined with time-restricted eating of less than ten hours a day, in women who are contemplating pregnancy and have risk factors for GDM [22].…”
mentioning
confidence: 99%